THE EFFECT OF GESTALT PLAY THERAPY WITH DRAWING MEDIA ON CREATIVITY IN HIGH SCHOOL STUDENTS - Tania Dhali Shonnareta (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2021)
In-play therapy, children in complex situations come to express and make some sense of their experiences. The purpose of this study is to try to help teachers adapt guidance and counseling learning with Gestalt play therapy, using picture media. The descriptive method was chosen because the research carried out aimed at describing the data naturally to make factual and accurate descriptions of the data, the nature of the data, and the relationship between the phenomena under study. Play therapy gestalt by drawing develops to help children who are unable to express thoughts and feelings through words. This can be a reference for guidance and counseling services, by playing but it can help solve one of the counselee's problems.